Parathyroid Diseases and Animal Models - Imanishi, Yasuo; Nagata, Yuki; Inaba, Masaaki (Frontiers in Endocrinology, 2012)
Circulating calcium and phosphate are tightly regulated by 3 hormones: the active form of vitamin D (1,25-dihydroxyvitamin D), fibroblast growth factor (FGF)-23, and parathyroid hormone (PTH). PTH acts to stimulate a rapid increment in serum calcium and has a crucial role in calcium homeostasis. Major target organs of PTH are kidney and bone. The oversecretion of the hormone results in hypercalcemia, caused by increased intestinal calcium absorption, reduced renal calcium clearance, and mobilization of calcium from bone in primary hyperparathyroidism. In chronic kidney disease, secondary hyperparathyroidism of uremia is observed in its early stages, and early stages, and this finally develops into the autonomous secretion of PTH during maintenance hemodialysis. Receptors in parathyroid cells, such as the calcium-sensing receptor, vitamin D receptor, and FGF receptor (FGFR)-Klotho complex have crucial roles in the regulation of PTH secretion. Genes such as Cyclin D1, RET, MEN1, HRPT2, and CDKN1B have been identified in parathyroid diseases. Genetically engineered animals with these receptors and the associated genes have provided us with valuable information on the patho-physiology of parathyroid diseases. The application of these animal models is significant for the development of new therapies.